Romidepsin (FK228) fails in counteracting the transformed phenotype of rhabdomyosarcoma cells but efficiently radiosensitizes, in vitro and in vivo, the alveolar phenotype subtype. (3rd July 2021) - Rossetti, Alessandra; Petragnano, Francesco; Milazzo, Luisa; Vulcano, Francesca; Macioce, Giampiero; Codenotti, Silvia; Cassandri, Matteo; Pomella, Silvia; Cicchetti, Francesca; Fasciani, Irene; Antinozzi, Cristina; Di Luigi, Luigi; et al.
Abstract: Purpose: Herein we describe the in vitro and in vivo activity of FK228 (Romidepsin), an inhibitor of class I HDACs, in counteracting and radiosensitizing embryonal (ERMS, fusion-negative) and alveolar (ARMS, fusion-positive) rhabdomyosarcoma (RMS). Methods: RH30 (ARMS, fusion-positive) and RD (ERMS, fusion-negative) cell lines and human multipotent mesenchymal stromal cells (HMSC) were used. Flow cytometry analysis, RT-qPCR, western blotting and enzymatic assays were performed. Irradiation was delivered by using an x-6 MV photon linear accelerator. FK228 (1.2 mg/kg) in vivo activity, combined or not with radiation therapy (2 Gy), was assessed in murine xenografts. Results: Compared to HMSC, RMS expressed low levels of class I HDACs. In vitro, FK228, as single agents, reversibly downregulated class I HDACs expression and activity and induced oxidative stress, DNA damage and a concomitant growth arrest associated with PARP-1-mediated transient non-apoptotic cell death. Surviving cells upregulated the expression of cyclin A, B, D1, p27, Myc and activated PI3K/Akt/mTOR and MAPK signaling, known to be differently involved in cancer chemoresistance. Interestingly, while no radiosensitizing effects were detected, in vitro or in vivo, on RD cells, FK228 markedly radiosensitized RH30 cells by impairing antioxidant and DSBs repair pathways in vitro. Further, FK228 when combined with RT in vivo significantly reduced tumor mass in mouse RH30 xenografts. Conclusion: FK228 did not show antitumor activity as a single agent whilst its combination with RT resulted in radiosensitization of fusion-positive RMS cells, thus representing a possible strategy for the treatment of the most aggressive RMS subtype.